Islamic Legal Hybridity in the Mappatoi System: Sharia Economic Adaptation among Minority Muslim Communities in Plural Society - Qamaruddin, Muh. Yusuf; Salju, Salju; Harahap, Burhanuddin; Tamami, Ahmad; Isman, Ainul Fatha; Katman, Muhammad Nasri; Wan Zulkiffli, Wan Farha binti (IAIN Manado, 2025)
This study analyzes the implementation of Islamic economic principles in the mappatoi system as a form of sharia economic adaptation among minority Muslim communities in Cendana Putih 1 Village, North Luwu, living in a plural society dominated by Hindu customary systems. The research employs a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with Muslim and Hindu farmers, and document analysis. Data analysis utilized a descriptive-qualitative approach with a fiqh al-aqalliyyat framework. Findings reveal the phenomenon of